2022
DOI: 10.3390/s22197450
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Non-Invasive Approach to Evaluating Soil Moisture without Soil Disturbances: Contactless Ultrasonic System

Abstract: Soil moisture has been considered a key variable in governing the terrestrial ecosystem. However, it is challenging to preserve indigenous soil characteristics using conventional soil moisture monitoring methods that require maximum soil contacts. To overcome this issue, we developed a non-destructive method of evaluating soil moisture using a contactless ultrasonic system. This system was designed to measure leaky Rayleigh waves at the air–soil joint-half space. The influences of soil moisture on leaky Raylei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Several studies have explored the influences of soil moisture on soil surface waves (Flammer et al., 2001; Lo et al., 2007; Lu & Sabatier, 2009; Woo et al., 2022; Pan et al., 2022). Lu and Sabatier (2009) found that other environmental factors, compared to soil water potential, had less influence on the sound speed in the soil, as sound speeds exhibited a power law dependency on soil water potentials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have explored the influences of soil moisture on soil surface waves (Flammer et al., 2001; Lo et al., 2007; Lu & Sabatier, 2009; Woo et al., 2022; Pan et al., 2022). Lu and Sabatier (2009) found that other environmental factors, compared to soil water potential, had less influence on the sound speed in the soil, as sound speeds exhibited a power law dependency on soil water potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The signals were averaged over 100 consecutive events to minimize unintended bias and error, and we saved the signals every 5 min. Those who require a detailed understanding of the ultrasonic system, including circuit configurations and equations, can refer to previous studies (Hong & Choi, 2021; Hong et al., 2020; Woo et al., 2022). To account for the slight variation in speed of ultrasonic waves between the air and soil, particularly under saturated clay, an acoustic barrier was placed between the transmitter and receivers, although the speed of the leaky Rayleigh wave was contingent upon the degree of soil moisture (Dashwood et al., 2020; Yang, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations